Outside Back Cover: Volume 4 Issue 1. Issue 1 (26th December 2022) - Wang, Fu‐Dong; Yu, Mei‐Xi; Chen, Xu‐Dong; Li, Jiaqiang; Zhang, Zhi‐Cheng; Li, Yuan; Zhang, Guo‐Xin; Shi, Ke; Shi, Lei; Zhang, Min; Lu, Tong‐Bu; Zhang, Jin
Abstract : Outside back cover image : An optically modulated dual‐mode memristor array based on core‐shell CsPbBr3 @graphdiyne nanocrystals is developed, which can emulate both the artificial synapses and neurons in the dark and illumination conditions, respectively. Based on this dual‐mode memristor, a power‐free artificial nociceptive signal processing system and a spiking neural network are developed, in which the nociceptors, spiking neurons and artificial synapses are implemented by our dual‐mode memristors. This is the first demonstration of fully memristive neuromorphic computing hardware at the system level comprising only one kind of memristors, significantly simplifing the fabrication and integration of fully memristive neuromorphic computing hardware. (DOI: https://doi.org/10.1002/smm2.1135 )